Efficient rational modification of non-ribosomal peptides by adenylation domain substitution - Mark J. Calcott (Nature Portfolio, 2020)
Non-ribosomal peptide synthases are multimodular enzymes comprised of adenylation (A), condensation (C) and thiolation domains. Here, the authors show that non-ribosomal peptides can be generated solely by A domain substitutions, providing evidence that the postulated substrate specifying role of C-domains may be rare in nature.